Transverse Cracking of Concrete Base Plate in CRTS III Ballastless Track Structure: Effects of Environmental Boundary Conditions - Weiqiang Guo (MDPI AG, 2021)
The cast-in-place concrete base plate is a main member of the China Railway Track System (CRTS) III ballastless track structure that is prone to generating early transverse cracking. Such cracks can dramatically affect the performance and service life of the railway track structure. This study investigated the influence of temperature and moisture boundary conditions on early cracking behavior of the CRTS III base plate by using approaches of both in situ measurements and numerical modelling. In-site measurements of strain and temperature were made in four test series of CRTS III base plates under the same natural environmental condition but cured with different regimes, and a total of 96 measuring positions were monitored for up to 150 days. The results showed that the strain magnitude and distribution in the field base plate, the initial time at cracking, and the observed cracking pattern varied significantly between the different test series. In order to understand the mechanisms that create these transverse cracks and to provide guidelines for the current curing strategy during construction, the characteristics of temperature-induced and moisture-induced stresses were analyzed by using 3D numerical modelling and by considering early-age concrete creep properties, meteorological factors, and the influence from environmental boundary conditions. The calculated results revealed that early-age transverse cracking in CRTS III base plate depends more on drying shrinkage stress than temperature stress. By conducting this study, we expect to provide guidance for reducing or eliminating early cracks of CRTS III concrete base plate.